Dialect on trial: use of African American Vernacular English influences juror appraisals - Kurinec, Courtney A. (Psychology, crime & law, 2019)
We investigated the effect of dialect and race on juror decision making. Mock jurors read a summary of an ambiguous criminal case, which included audio of a defense witness (Study 1) or defendant (Study 2). Both speaker dialect [General American English (GAE)/African American Vernacular English (AAVE)] and race (White/Black) were crossed; Study 2 also included three levels of case (Ambiguous/Pro-Prosecution/Pro-Defense) to evaluate any effects of evidentiary context. In both studies, jurors who listened to the AAVE recording found the AAVE-speaking witness to be less professional and less educated than their GAE-speaking counterparts. Interestingly, jurors in Study 2 who heard the defendant use GAE were more likely to find him guilty and found him less credible when the case favored the prosecution, hinting that ingroup biases such as the black sheep effect may also play a role in perceptions of dialect. Secondary analyses found that AAVE predicted more negative overall evaluations of the speaker, and these negative evaluations were associated with an increase in guilty verdicts. Together, these findings suggest that dialect plays an under-investigated role in the courtroom, and that bias against AAVE negatively impacts juror appraisals of its speakers and can potentially influence juror decision making.